Case Report: A “senior” with serpentine-like syndrome—treatment of combined brachyoesophagus, intrathoracic stomach and cervical rachischisis - Lohmann, Judith; Freund, Anna; Klein, Tobias; Acero, Daniel; Boemers, Thomas (Frontiers in Pediatrics, 2024)
Serpentine-like syndrome, characterized by the combination of intrathoracic stomach, a notably short esophagus anomaly, splenic abnormalities, and cervical spine malformations, has been associated with a high mortality rate since its identification in 2008. This report presents the case of a remarkable patient who recently celebrated her fifth birthday, marking her as the oldest documented individual with this syndrome to date. Highlighting the significance of comprehensive evaluations for concurrent malformations, the report discusses potential treatment modalities and challenges inherent in managing patients with this intricate syndrome. A comprehensive review of previously published cases is provided, comparing surgical interventions, causes of death, and age at the time of demise. This report underscores the importance of ongoing research and collaborative efforts to optimize outcomes for individuals afflicted with serpentine-like syndrome.